Epidural Spinal Mass as the Presenting Feature of B-Acute Lymphoblastic Leukemia in a Young Child. Issue 8 (November 2020) - Chapman, Stacy; Li, Jie; Almiski, Muhamad; Moffat, Hayley; Israels, Sara J.
Abstract : An isolated epidural mass is a rare presentation of childhood B-acute lymphoblastic leukemia with an estimated incidence of 0.4%. Of the cases reported in the literature, the majority involve adults presenting with spinal cord compression and/or systemic evidence of disease. We describe a young child presenting with pain leading to a refusal to weight-bear secondary to a sacral epidural mass. A biopsy of the sacral lesion confirmed the diagnosis of B-acute lymphoblastic leukemia. Unique to this case is the young age of the child and the lack of spinal cord compression.